Graves Disease (Thyroid Storm) with Polyautoimmune Disorders (Autoimmune Hemolytic Anemia and Probable Autoimmune Hepatitis) - Mabruratussania Maherdika; Banundari Rachmawati; Andreas Arie Setiawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Graves' disease is caused by IgG antibodies that bind to the Thyroid Stimulating Hormone (TSH) receptor on the surfaceof the thyroid gland. These bonds drive the growth of stimulated thyroid follicular cells causing the glands to enlarge andincrease the production of thyroid hormones. Previous studies mention the association of HLA-B8 and HLA-DR3 withGraves' disease and the Cytotoxic T-lymphocyte-associated-4 (CTLA-4) gene on chromosome 2q33 as a result of reducingT-cell regulation, resulting in autoimmune disease. Autoimmune thyroid disease is often found together with otherautoimmune disorders (polyautoimmune). A 51-year-old male complained of dyspnea, yellowing of the body, and a lumpon the neck. One year ago, he was diagnosed with hyperthyroidism. Graves' disease was suspected due to a score of 22 forthe Wayne index, FT4 96.9 pmol/L, TSHs <0.01 μIU/mL, TRAb 10.8 IU/L, thyroid uptake test for toxic diffuse struma. Inaddition, the patient had atrial fibrillation and a thyroid storm with a Bruch Wartofsky index score of 65. Laboratoryexamination found normocytic normochromic anemia, thrombocytopenia, reticulocytosis, direct coomb test and autocontrol results positive one, SGOT 87 U/L, SGPT 59 U/L, alkali phosphatase 166 U/L, total bilirubin 38.13 mg/dL, directbilirubin 16.59 mg/dL, indirect bilirubin 21.54, LDH 318 U/L, establishing the diagnosis of Autoimmune Hemolytic Anemia(AIHA). Autoimmune hepatitis score: 15, so a diagnosis of probable autoimmune hepatitis was made.